Budo as philosophical background of Karate-Do: does the training method really matter? - Tomás, João (2019)
Background. The practice of Japanese originated martial arts, like Karate-Do, is associated with an individual “path of enlightment” or the way of living (Do), that surpasses the athletic practice for itself. The concept of Budo, with all values, moral principles and patterns of behaviour, is traditionally linked to this path or way, being the philosophical background of the practice. The globalisation of the Karate-Do have created two main ways or training methods with different main goals – traditional one and sports Karate-Do. Problem. The main objective of this study is to compare the evaluations of different Budo- associated aspects, values, principles and domains, to find the differences between karateka who are engaged in both training methods. Method. A questionnaire was applied, in Portugal, to a group of 78 karateka with more than two years of continued training, who are engaged or use a traditional or sports training method. Results. The results show a high and similar evaluation scores of all items questioned on both training methods, only with single and not consistent differences. Conclusion. Without generalising, we can assume that karateka observe the philosophical background of Karate-Do (Budo) in only one way, even when they are engaged in different methods of practice with different main goals. So, Karate-Do philosophy is one,only daily practices in dojo and goals differ. However, further investigation is needed to support these conclusions.